2020
DOI: 10.1002/jbmr.3935
|View full text |Cite
|
Sign up to set email alerts
|

Association of Tramadol Use With Risk of Hip Fracture

Abstract: Several professional organizations have recommended tramadol as one of the first‐line or second‐line therapies for patients with chronic noncancer pain and its prescription has been increasing rapidly worldwide; however, the safety profile of tramadol, such as risk of fracture, remains unclear. This study aimed to examine the association of tramadol with risk of hip fracture. Among individuals age 50 years or older without a history of hip fracture, cancer, or opioid use disorder in The Health Improvement Netw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(51 citation statements)
references
References 54 publications
(127 reference statements)
2
48
0
1
Order By: Relevance
“…As suggested by a recent meta-analysis on the comparative effectiveness of NSAIDs and opioid use for knee OA, there is no statistically significant difference in pain relief between tramadol and NSAIDs among OA patients [ 13 ]; however, tramadol is associated with more opioid-related adverse effects, for example, nausea, dizziness, constipation, tiredness, headache, vomiting, and drowsiness [ 14 ]. Several studies have compared risks of serious adverse events between tramadol and alternative commonly prescribed analgesics in patients with OA using the Health Improvement Network data that includes 6% of the UK population [ 11 , 15 , 16 ]. These studies showed that tramadol was associated with a significantly higher risk of mortality, myocardial infarction (MI), and hip fractures as compared to commonly prescribed NSAIDs.…”
Section: Introductionmentioning
confidence: 99%
“…As suggested by a recent meta-analysis on the comparative effectiveness of NSAIDs and opioid use for knee OA, there is no statistically significant difference in pain relief between tramadol and NSAIDs among OA patients [ 13 ]; however, tramadol is associated with more opioid-related adverse effects, for example, nausea, dizziness, constipation, tiredness, headache, vomiting, and drowsiness [ 14 ]. Several studies have compared risks of serious adverse events between tramadol and alternative commonly prescribed analgesics in patients with OA using the Health Improvement Network data that includes 6% of the UK population [ 11 , 15 , 16 ]. These studies showed that tramadol was associated with a significantly higher risk of mortality, myocardial infarction (MI), and hip fractures as compared to commonly prescribed NSAIDs.…”
Section: Introductionmentioning
confidence: 99%
“…This pattern of treatment may be emerging as a substitute for non-steroidal anti-inflammatory drugs and strong opioids due to the growing concern about their risks. Whatever the reason, this finding suggests a generalized perception in our setting of tramadol as "opioidlite," with minimal side effects or propensity for addiction and misuse (Stannard, 2019); this perception contrasts with growing evidence of its adverse effects (Fournier et al, 2015;Zeng et al, 2019;Wei et al, 2020) and addictive potential (Thiels et al, 2019). Third, from 2016 the curve of annual opioid treatments started to flatten, mainly due to the slow-down in tramadol and fentanyl prescriptions.…”
Section: Discussionmentioning
confidence: 85%
“…Tapentadol is unique in pharmacologic and pharmacokinetic profiles and can be a valuable option in cases of significant widespread opioid intolerance, but is completely reliant on renal function for excretion. While tramadol is also sometimes considered in patients with intolerance to preferred opioids, its diverse receptor profile confers increased adverse event risks that are especially undesirable in the postoperative period, in addition to previously discussed risks related to its metabolic pathways [417,[420][421][422][423][424][425][426][427][428]. Pharmacists can also assess medication regimens for clinically significant drug-drug pharmacokinetic interactions, especially in patients on antiepileptic medications, azole antifungals, or rifampin [413,429,430].…”
Section: Postoperative Opioid Considerationsmentioning
confidence: 99%